The role of gender in educational contexts and outcomes - Liben, Lynn S.; Bigler, Rebecca S. (Advances in child development and behavior, 2014)
"Volume 47 of Advances in Child Development and Behavior includes chapters that highlight some the most recent research in the area of gender in educational, contexts and outcomes. A wide array of topics are discussed in detail, including sexism, race and gender issues, sexual orientation, single-sex education, and physical education. Each chapter provides in-depth discussions, and this volume serves as an invaluable resource for developmental or educational psychology researchers, scholars, and students."--EBL choice